Early Christians adapting to the Roman Empire: mutual recognition - Huttunen, Niko (Novum Testamentum / Supplements, 2020)
Preface -- 1 Introduction: Recognition between Anti- and Pro-Imperial Readings -- 2 Imperial Recognition in the Intellectual Sphere: Christians and Philosophers -- 1 Almost Philosophers: Pagan Philosophers Recognizing Christians -- 2 Early Christians Seeking Recognition in Greco-Roman Culture -- 3 Imagination Made Real: Paul between Political Realism and Eschatological Hope -- 1 Paul and His Readers -- 2 Paul's Realism and Imagination -- 4 Brothers in Arms: Soldiers in Early Christianity -- 1 Soldiers in the Gospels Contextualized -- 2 Metaphors, Antimilitarism, and Christian Soldiers -- 5 Conclusions -- Bibliography -- Index -- .